A RE-AIM Analysis of an Intergenerational Dementia Education Program - Smith, Ashleigh E.; Kamm, Georgina L.; Lai, Samantha; Hull, Melissa J.; Baker, Jess R.; Milte, Rachel; Ratcliffe, Julie; Loetscher, Tobias; Keage, Hannah A. D. (Frontiers in Public Health, 2020)
Objectives: Children often have a lack of dementia understanding and poor attitudes toward people with dementia. Intergenerational programs are increasingly common, but the effects on knowledge and attitudes related to dementia are mixed, especially in the long-term (6 months). Using a RE-AIM framework, we quantitatively evaluated the effects of an educational dementia program (with and without an intergenerational program) on dementia attitudes in the short and long-term, and qualitatively, which elements of the program facilitated this change. Methods: Eighty-one children (9.63±0.52 years, 35 males) from three classes participated in an 8-week dementia education program and 52 also interacted with older adults through an intergenerational experience. Program reach was measured as the percentage of children who participated in the study. The Kids Insight into Dementia Survey (KIDS) was implemented to measure dementia knowledge and attitudes: efficacy and maintenance. Qualitative interviews with all participant groups informed both adoption and implementation. Cost-benefit analysis was used as a secondary outcome measure for efficacy. Results: The program demonstrated strong levels of impact reaching 93% of school children across the three included classes. Efficacy was demonstrated by a positive change in children’s dementia knowledge and attitudes immediately post program, which remained increased (as compared to baseline) 6- months post intervention; there were no differences between groups (those who interacted with older adults and those who did not). Interviews identified positive changes in children’s empathy and improved community awareness. Barriers to adoption included the project scope, time constraints incurred by school terms and the management of children-to-adult ratios. Conclusions: These findings provide the first evidence that school-based dementia education improves knowledge of and attitudes towards people with dementia long-term. We demonstrated programs such as this can be successful in both primary school and wider community settings, with support from school and community partners key to the success.